Paixão ou vocação?: competência jornalística, redes de relações e atuação na assessoria de imprensa política em Aracaju - Souza, Isabel Rocha (2013)
The present dissertation has as object of study the relationship between the journalistic competence2, the relationship networks and the insertion of journalists in the Aracaju´s politic press office. In the attempt of understanding how this professional is inserted and rises professionaly in this space of social communication, we start from the principle that personal and interpersonal ties may constitute a prime resource for entry into the politic press office and the occupation of headship position in comunication office in governmental and legislative institutions. In order to do this objective, it was adopted as data collection the biographical research with journalists working in press offices in the political sphere. The empirical universe considered is formed by 10 journalists, wich 04 of them direct sectors in governmental and legislative organizations and the other 06 ones advise politician and parliamentarians. The analysis reveals that the entry of the journalist in the field of politic press in Aracaju, is through nominations made by a friend, a relative, or a professional colleague, a known political, or through personal invitations. It also indicates that the links created through political activism, may result in invitations to occupy positions in state agencies.